1989
DOI: 10.1002/neu.480200803
|View full text |Cite
|
Sign up to set email alerts
|

Autoradiographic identification of ecdysteroid‐binding cells in the nervous system of the moth Manduca sexta

Abstract: The steroid hormone 20-hydroxyecdysone regulates many aspects of nervous system development in the moth Manduca sexta, including stage-specific neuronal morphology and stage-specific neuronal death. We have used steroid hormone autoradiography to study the distribution of cells that concentrate ecdysteroids in the ventral nervous system of this insect. The ligand was [3H]-ponasterone A, a bioactive phytoecdysone. Tissue was examined from three stages of development: the end of larval life (first day of wanderi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…The two most striking characteristics of the doomed neurons revealed in the present study are that they exhibit approximately 10-fold higher EcR levels than do other central neurons, and that this elevated expression is due to a single receptor isoform, EcR-A. This result is consistent with autoradiographic studies of the binding of radiolabeled ecdysteroids in Manduca, which showed that doomed neurons had greater steroid-binding capacity than did other neurons (Fahrbach and Truman, 1989). The potential importance of the finding that doomed neurons exhibit a high abundance of EcR-A is highlighted by the observation that the pupal-adult molt represents the only stage in the life of these cells when EcR-A is the predominant isoform (J. W. T., W. S. T., and D. S. H., unpublished data).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The two most striking characteristics of the doomed neurons revealed in the present study are that they exhibit approximately 10-fold higher EcR levels than do other central neurons, and that this elevated expression is due to a single receptor isoform, EcR-A. This result is consistent with autoradiographic studies of the binding of radiolabeled ecdysteroids in Manduca, which showed that doomed neurons had greater steroid-binding capacity than did other neurons (Fahrbach and Truman, 1989). The potential importance of the finding that doomed neurons exhibit a high abundance of EcR-A is highlighted by the observation that the pupal-adult molt represents the only stage in the life of these cells when EcR-A is the predominant isoform (J. W. T., W. S. T., and D. S. H., unpublished data).…”
Section: Discussionsupporting
confidence: 89%
“…receptor than those that survive (Fahrbach and Truman, 1989). Could quantitative differences in receptor levels control the hormonally regulated aspects of this developmental decision?…”
Section: Introductionmentioning
confidence: 99%
“…I f) tritocerebrum displayed intense c-fos-like immunoreactivity, in contrast to days 1-3 when they were either not stained or only very weakly stained. The latter neurons probably represent neurosecretory cells and/or motoneurons regarding to their size (Fahrbach and Truman 1989) and location.…”
Section: Resultsmentioning
confidence: 99%
“…This was first suggested many years ago by the ecdysteroid-induced puffing of dipteran salivary gland chromosomes (Clever and Karlson 1960;Ashburner et al 1974) and has more recently been demonstrated autoradiographically by the developmentally specific expression of nuclear ecdysteroid binding sites in the central nervous system and endocrine glands of the fly Calliphora vicina (Bidmon and Koolman 1989) and the larvae and pupae of a moth, Manduca sexta (Fahrbach and Truman 1989;Bidmon et al 1990aBidmon et al , b, 1991Bidmon and Sliter 1990). In all these studies, binding sites appeared at developmental time points critical for the action of ecdysteroids Offprint requests to: H.-J.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on cultured leg MNs indicated that 20E enhances the complexity of process branching (Prugh et al, 1992;Matheson and Levine, 1999). In addition, both autoradiographic and immunolocalization studies indicate that MNs express ecdysone receptors (Fahrbach and Truman, 1989;Fahrbach, 1992;Truman et al, 1994). Expression of one isoform (EcR-B1) is associated with regressive aspects of remodeling, while expression of another (EcR-A) is associated with growth (Truman et al, 1994).…”
Section: Mechanisms Of Central Influences On Dendritic Growthmentioning
confidence: 95%